(untitled) (Eurasian Journal of Philology Science and Education, 2016)
Nowadays translator-specialists are interested in investigating translator’s brain process during translation. They worked out frame approach to understand this process without high technological equipment. This approach helps precisely investigate the conceptual components and comparing them understand the process of brain work. It is worth noting that the approach does not just present steps of brain work but also justifies adequacy in communicative process.